PREACHING THROUGH SOCIAL MEDIA IN ISLAMIC RELIGIOUS EDUCATION: ANALYSIS OF EFFECTIVENESS AND CHALLENGES IN INCREASING RELIGIOUS AWARENESS - Wahyuningsih, Fitri; Hakki, Saddam; Susanti, Riri (PT. Antis International Publisher, 2025)
Objective: This study aims to describe and analyze the effectiveness and challenges of using social media as a medium for da'wah in Islamic religious education, particularly in enhancing religious awareness. Method: Employing a library research approach, this study draws upon books, peer-reviewed journal articles, and research reports as primary data sources. Results: The findings indicate that da'wah through social media is effective in raising religious awareness, especially among younger audiences, when delivered through creative formats such as short videos and live streaming. Effective strategies to optimize its use include the creation of engaging content, enhancing the digital literacy of preachers (da'is), fostering collaborations with influencers, and maintaining active interaction with audiences. However, challenges persist, including the potential spread of inaccurate religious information, limited digital competence among da'is, public skepticism toward digital da'wah, and unsupportive social media algorithms. Novelty: This research highlights the dual role of social media as both an opportunity and a challenge for Islamic religious education, offering insights into how strategic digital engagement can transform traditional da'wah practices to meet contemporary needs.